Inductive link modeling and design guidelines for optimum power transfer in implantable wireless microsystems - Wan Salim, Wan Wardatul Amani; Baldi, Antonio; Ziaie, Babak (IEEE, 2005)
In this paper, we present a new approach for wireless link modeling in inductively powered microsystems. We will also pronde design guidelines for obtaining a maximum coupling coefficient and achieving minimum misalignment sensitivity between an integrated micro-coil and an external planar coil. Maxwell" 3D simulations are used to model the link and to calculate the coupling coeffcient between the coils. For analysis and design, both coils are assumed to be planar and square. The simulations are performed for completely aligned, laterally misaligned, angularly misaligned, and laterally/angularly misaligned coils. It is shown that external coil dimensions are an important design parameter for optimum coupling at fixed separations. Experimental and simulation results are shown to be in good agreement to within less than 5%.